Electrochemically Engineering of Nanoporous Materials - Abel Santos (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. Electrochemical engineering of nanoporous materials is a cost-effective and facile synthesis approach that enables the production of a range of nanoscale materials with controllable dimensions and properties. Recent decades have witnessed extensive research activity into the advanced engineering of nanoporous materials, from fundamental studies to applied science. These nanomaterials offer a set of unique and exclusive advantages for a wealth of applications, including catalysis, energy storage and harvesting, electronics, photonics, sensing, templates, and membranes. This Special Issue is dedicated to recent research advances in electrochemical engineering of nanoporous materials and their application across several disciplines and research fields. The broad and interdisciplinary applicability of these nanomaterials will be of profound and immediate interest for a broad audience, ranging from physicists, chemists, engineers, materials scientists, bioengineers, and nanomedicine experts.